A new freshwater goby, Rhinogobius lianchengensis (Teleostei: Gobiidae) from the Minjiang river basin, Fujian Province, China - Wang, Shen-Chih; Chen, I-Shiung (Zootaxa, 2022)
A new freshwater goby of Rhinogobius Gill, 1859, were collected from the Minjiang river basin, Fujian Province, PR China. The new goby, Rhinogobius lianchengensis n. sp. can be well distinguished from other congeneric species by the following combination of features: second dorsal fin I/8; anal fin I/6-7; pectoral fin modally 16–17; longitudinal scale rows 33–34; predorsal scales 0–3; vertebral count 27; and specific coloration pattern: scale pocket of lateral body with distal brown to blackish brown mark; cheek deep brown on dorsal half with 7–8 somewhat parallel oblique deep brown bars after the vertical stripe on snout in male; opercle brown to yellowish brown with net-like deep brown marks in both sexes; branchiostegal membrane bright yellow background with 16-19 deep red or brownish red spots in male; first dorsal fin with a black mark in male; pectoral fin base with a median patch of blackish spots surrounding with some irregularly large brown marks; and caudal fin yellow with 3–4 vertical rows of deep brown spots. A diagnostic key to all nominal Rhinogobius species from Fujian Province, PR China is provided.